Is there an optimal ischemic-preconditioning dose to improve cycling performance? - Cocking, S.; Wilson, M. G.; Nichols, D.; Cable, N. T.; Green, D. J.; Thijssen, D. H. J.; Jones, H. (International Journal of Sports Physiology and Performance, 2018)
Introduction: Ischemic preconditioning (IPC) may enhance endurance performance. No previous study has directly compared distinct IPC protocols for optimal benefit. Purpose: To determine whether a specific IPC protocol (ie, number of cycles, amount of muscle tissue, and local vs remote occlusion) elicits greater performance outcomes. Methods: Twelve cyclists performed 5 different IPC protocols 30 min before a blinded 375-kJ cycling time trial (TT) in a laboratory. Responses to traditional IPC (4×5-min legs) were compared with those to 8×5-min legs and sham (dose cycles), 4×5-min unilateral legs (dose tissue), and 4 × 5-min arms (remote). Rating of perceived exertion and blood lactate were recorded at each 25% TT completion. Power (W), heart rate (beats/min), and oxygen uptake (VO2 ) (mL/kg·min) were measured continuously throughout TTs. Magnitude-based-inference statistics were employed to compare variable differences to the minimal practically important difference. Results: Traditional IPC was associated with a 17-s (0, 34) faster TT time than sham. Applying more dose cycles (8×5 min) had no impact on performance. Traditional IPC was associated with likely trivial higher blood lactate and possibly beneficial lower VO2 responses vs sham. Unilateral IPC was associated with 18-s (-11, 48) slower performance than bilateral (dose tissue). TT times after remote and local IPC were not different (0 [-16, 16] s). Conclusion: The traditional 4 × 5-min (local or remote) IPC stimulus resulted in the fastest TT time compared with sham; there was no benefit of applying a greater number of cycles or employing unilateral IPC.